Mechanically induced defects in milled CdZnSe nanocrystal: a low-temperature electron spin resonance spectroscopy analysis - Muh'd, Ibrahim Bagudo; Talib, Zainal Abidin; Liew, Josephine Ying Chyi (Elsevier, 2017)
The electron spin resonance (ESR) linewidth of the milled powder decreases as a function of increasing temperature. On the other hand, the intensity of the signal increases with increasing temperature from 108 K to 243 K and subsequently approaches Curie-like temperature behavior above 245 K. These behaviors were understood in terms of the orbital degeneracy of fast-relaxing impurities, such as Fe3+ ion debris, from the grinding media that was embedded in the atomic structure of the milled powder and are not completely quenched. At lower temperature, only ±1/2 is occupied and the excited energy state is less likely effective in dipolar broadening compared with lower energy states of ±5/2 and ±3/2. In this regard, decrease in linewidth should be expected with increasing temperature.